Peran Model Kepemimpinan Karismatik Dalam Meningkatkan Kinerja Karyawan (Studi Pada Baitul Mal Wa Tamwil (BMT) Muamalah Tulungagung) - Solihin, Misbakhul Khaer; Basuki, Ahmad (Program Studi Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam IAIN Kediri, 2023)
In conducting a sharia financial institution, especially Baitul Mal Wa Tamwil (BMT) the leader holds an important position in the organization. A leader has the power to make rules or policies that must be adhered to and implemented by subordinates or employees. In addition, the leadership model implemented by leaders can affect employee performance. Based on this background, a problem formulation can be taken related to the role of charismatic leadership models in improving employee performance at Baitul Mal Wa Tamwil (BMT) Muamalah Tulungagung and supporting factors and inhibitions in improving employee performance at Baitul Mal Wa Tamwil (BMT) Muamalah Tulungagung. The research that the authors conducted is included in qualitative research, included in the type of field research, and using a descriptive approach. The results of the research conducted by the author can be conveyed here that the charismatic leadership model is applied by the leader of Baitul Mal Wa Tamwil (BMT) Muamalah Tulungagung. have a role to play in improving employee performance. With the charisma that exists in the leader Baitul Mal Wa Tamwil (BMT) Muamalah Tulungagung can influence employees so as to encourage or motivate employees to carry out their duties and responsibilities well, and the performance of employees is increasing. The effectiveness of resources, motivation and work environment are supporting and inhibitory factors in improving employee performance at Baitul Mal Wa Tamwil (BMT) Muamalah Tulungagung.